BASKET MARKET ANALYSIS USING R-BASED APRIORI ALGORITHM TO FIND INFORMATION FROM SALES DATA - Indra Yustiana; Irvan Sutarha; Nindia Maulawati; Ilham Maulana Yusuf (Nusa Putra University, 2021)
Market Basket Analysis is a data mining technique that is used to determine which products a customer will buy simultaneously by analyzing a list of customer transactions. By knowing these products, an e-commerce system can create or develop a customer profile system and can determine its own customer catalog layout. This journal discusses data mining techniques, with association rules that can help check customer buying behavior and increase sales. The result can provide reference prices for cross selling, designing promotions and placing merchandise in stores increasing sales